NEW VIEWS ON THE MECHANISM OF HERD GENERAL ADAPTATION SYNDROME INFLUENCED BY LIMIT PHYSICAL ACTIVITY - Korytko, Z.I. (World of Medicine and Biology, 2013)
The review analyzed classical and modern literature on the mechanisms of adaptation to extreme factors. Key role in the mechanisms of adaptation assigned analyze classical version of general adaptation syndrome by Hans Selye, and given recent data that complement the classic description of the three stages of non-specific component of the stress response. New views on the mechanisms of development stages of general adaptation syndrome by H. Selye made based on analysis of current literature data and the results of their research on the model by limiting physical activity.